POLITICAL VIEWS OF K. SCHMITT IN THE FRAMEWORK OF ESTABLISHING A MODERN RULE-OF-LAW STATE - Шумський, Л. М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
K. Schmitt’s position presents a certain complex of means for forming adequate approaches to political realities of modernity, especially by fulfilling the tasks of establishing a democratic rule-of-law state. Schmitt’s heritage provide a huge potential intellectual contribution to understanding the logics of modern political science where new approaches are gained to interpreting the concepts of legality and legitimacy of the state’ governing, of totality and a strong state. The topicality of the issues of political unity of a society is supported, which Schmitt connects to the phenomenon of representativeness.